Conformance and performance roles of bank boards: The connection between non-performing loans and non-performing directorships. Issue 5 (October 2019) - Lafuente, Esteban; Vaillant, Yancy; Vendrell-Herrero, Ferran
Abstract: This study evaluates how non-performing loans and different types of board turnover—which we link to performing directorship (natural turnover) and non-performing directorship (forced turnover)—impact the economic performance (ROA) of banks. The proposed model and hypotheses, based on the conformance and performance roles of boards, are tested on a rich sample that includes all banking firms operating in Costa Rica between 2000 and 2012. The results indicate that the negative effect of non-performing loans on ROA is significantly greater in banks with non-performing directorship associated with high rates of unexpected changes in the board. The findings of the study highlight that the competence of boards matters. The results also give evidence of the importance of balancing financial and non-financial goals if superior governance and economic performance are the objectives pursued by organisations.